(3EYQGH GdebOeI GdCLQhejIs - (3GHf GLQhe , CHh YHO Gddg eMeO Hf eMeO Hf OGhO GdUfgGLj,J (B723 (3g` s
(3ChdgG (B:s
(3hde JLYdg NHQkG KGfjkG dg hCbSGeg eHJOC hjVGa Edjg KdGKI NHQg hGSe haYd hMQa HOd ef KdGKI HOd eaUd ef eLed s
(3BNQgG (B:s
(3HGH eYWha Ydi KhH hSGL eYWha Ydi HGH hNGJe eYWha Ydi KhH CjVkG haVI eVGa Edjg NGJeI hHGdNGJeI fNJe GdcJGH hGdMeO ddg GdPi CgOGfG heG dgPG cfG fgJOi dhdG Cf CgOGfG Gddg Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B33 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B215s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdfMhs